2020
DOI: 10.1002/cctc.202000396
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of C4 Olefins from Acetylene over Supported Copper Catalysts

Abstract: Conversion of acetylene to C4 olefins enables on‐purpose synthesis of C4 olefins using abundant natural gas resource due to acetylene can be synthesized from methane or ethane. In this study, Cu‐based catalysts supported on SiO2, ZSM‐5 and mordenite (MOR) were tested for acetylene hydrodimerization. Effect of promoters including Ru, Ga, Ag and Pd on the acetylene conversion and C4 olefins selectivity are investigated. The structures of these catalysts were characterized by TEM, XRD, BET, H2‐TPR, NH3‐TPD and XP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In a previous study, we demonstrated the reaction of acetylene with ethylene to form butadiene, using commercially available molecular catalysts dissolved in a suitable solvent, revealing the possibilities opened up by the high reactivity of acetylene. The use of liquid media and molecular catalysts has so far been the preferred way of converting acetylene, , while solid-catalyzed reactions of gaseous acetylene have only rarely been studied. A recent study reported the formation of C 4 -olefins from acetylene over copper confined in the pores of metal–organic frameworks. However, the information in this manuscript is insufficient to assess catalytic activity.…”
mentioning
confidence: 99%
“…In a previous study, we demonstrated the reaction of acetylene with ethylene to form butadiene, using commercially available molecular catalysts dissolved in a suitable solvent, revealing the possibilities opened up by the high reactivity of acetylene. The use of liquid media and molecular catalysts has so far been the preferred way of converting acetylene, , while solid-catalyzed reactions of gaseous acetylene have only rarely been studied. A recent study reported the formation of C 4 -olefins from acetylene over copper confined in the pores of metal–organic frameworks. However, the information in this manuscript is insufficient to assess catalytic activity.…”
mentioning
confidence: 99%